BUDAYA PELESTARIAN LINGKUNGAN (EKOSISTEM) BERBASIS KEARIFAN LOKAL DI WILAYAH KEPULAUAN (SEBUAH PEMIKIRAN GLOBAL DALAM TINDAKAN LOKAL) - Max Maswekan; Korneles Balak (JURNAL BADATI, 2024)
The culture of "Sasi" is still practiced in every village/state in Maluku, including the Tanimbar Islands Regency (KKT), not excluding the village of Watidal. Sasi is "a prohibition on taking marine or terrestrial resources for a certain period with the aim of ensuring that marine or agricultural products have good and sustainable quality." Sasi is generally carried out in two forms, namely "Customary Sasi" or "State/Village Sasi" and "Church Sasi." This sasi tradition has long been a culture generally practiced in the lives of the Maluku people, particularly in the Tanimbar Islands. If viewed from the perspective of modern resource management, sasi is actually a form of "traditional management" that has been practiced since ancient times. Sasi is also one form of local wisdom that contains social, economic, legal, cultural, religious, and ecological values and dimensions. Sasi, when paralleled with modern thinking regarding environmental aspects, can be said to be a form of local community-based management (LCBM) in the context of reducing global warming. This means that sasi is one of the wise and prudent actions to preserve the earth from extinction (ecosystem sustainability) to mitigate climate change, which has been practiced by the people of Maluku in general, and Tanimbar in particular, including in the village of Watidal since ancient times. Karena itu, sasi seharusnya mendapatkan perhatian khusus dari pemerintah dan pecinta lingkungan. (green society).